Problematika Guru dan Dosen dalam Sistem Pendidikan di Indonesia - Rohman, Miftahur (IAIN Ponorogo, 2016)
This paper highlights educator problem in education system in Indonesia. The discussion focuses on general education and religious education. Educators of non-religious education are product of education and institute of teacher training and education (IKIP) which teach general science, meanwhile educators of religious education are product of Islamic Higher Education (PTKI) which teach religious knowledge. This study aims to analyze books, rules, researches, and news about teacher. To sum up, the educator problems include: poor quality teacher and low teacher salaries that are caused by some factors, government policy that is not implemented well, teacher training institution (LPTK) that are not able to produce a professional teacherØØ§ÙÙØª ÙØ°Ù Ø§ÙÙ ÙØ§ÙØ© Ø¯Ø±Ø§Ø³Ø© Ù Ø´Ø§ÙÙ Ø§ÙÙ Ø±Ø¨ÙÙÙ ÙÙ Ø¶ÙØ¡ Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù. ÙØ±ÙÙÙØ²Øª Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¹Ø§Ù Ø© ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ©. ÙØ§Ù Ø§ÙÙ Ø¹ÙÙÙ ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¹Ø§Ù Ø© Ø®Ø±ÙÙØ¬ Ø§ÙÙ Ø¹ÙØ¯ Ø§ÙØ¹Ø§ÙÙ ÙÙÙ Ø¹ÙÙÙ ÙÙ ÙØ§ÙØ¹ÙÙÙ Ø§ÙØªØ±Ø¨ÙÙØ© Â IKIP Â Ø«Ù Ù ØªØºÙÙØ± ÙØ«ÙØ± Ù ÙÙØ§ Ø¥ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø§Øª Ø§ÙØªÙ ØªØ¯Ø±ÙØ³ Ø§ÙØ¹ÙÙÙ Ø§ÙØªØ¬Ø±ÙØ¨ÙØ© ÙØ§ÙÙÙÙÙØ© . Ø£Ù Ø§ Ù Ø¹ÙÙ ÙØ§ Ø§ÙØ¹ÙÙÙ Ø§ÙØ¯ÙÙÙØ© ÙØ®ÙØ±ÙÙØ¬ÙØ§ Ø§ÙØ¬Ø§Ù Ø¹Ø§Øª Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØªÙ ØªØ¯Ø±ÙØ³ Ø§ÙØ¹ÙÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ©. ÙÙØªØ¨Øª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹Ù Ø·Ø±ÙÙ ØªØÙÙÙ Ø§ÙÙØªØ¨Ø ÙØ§ÙÙÙØ§ÙÙÙØ ÙØ§ÙØ¨ØÙØ« Ø§ÙØ¹ÙÙ ÙØ©Ø ÙØ§ÙØ£Ø®Ø¨Ø§Ø± Ø¹Ù Ø§ÙÙ Ø¹ÙÙÙ ÙÙ. Ø§Ø³ØªØ®ÙØµØª Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ§ÙÙØ© : ÙÙØ¹ÙØ© Ø§ÙÙ Ø¯Ø±Ø³ÙÙ ÙØ±ÙØ§ÙÙØ© ØÙØ§ØªÙÙ Ø¶Ø¹ÙÙØªØ§Ù. ÙÙØ°Ù ÙØªÙØ¬Ø© Ù Ù Ø£Ù ÙØ±Ø§Ø±Ø§Øª Ø§ÙØÙÙÙ Ø© Ø§ÙØªÙ ÙÙ ØªØ·Ø¨ÙÙ Ø¬ÙØ¯Ø§Ø ÙØ§ÙÙ Ø¤Ø³Ø³Ø§Øª Ø§ÙØªØ±Ø¨ÙÙØ© Ø§ÙØ¹Ø§ÙÙØ© Â LPTK ÙÙ ØªÙÙ ÙØ¹ÙØ§ÙØ© ÙÙ Ø§ÙØªØ§Ø¬ Ø§ÙÙ Ø¹ÙÙÙ ÙÙ